Determinants of retirement confidence among working women in government agencies in Peninsular Malaysia - Teo, Tze Juen (2015)
A number of working women neglected the importance of retirement preparedness.This causes them to be less confident towards their retirement life. Past research indicated that women often perform at their lower level of retirement confidence than men. The purpose of this study is to determine the relationships between individual characteristics (age, education, marital status, and money adequacy), financial literacy,saving motives, financial management practices, and retirement confidence among working women in public sectors. The sample of the present study consisted of 447 working women in public agencies located in four states in Peninsular Malaysia, selected through multi stage sampling technique. Data was collected through self-administered questionnaires. Descriptive analysis, independent sample t-test, and multiple regression were used in the Statistical Software Package for Social Science (SPSS). The results of this study showed that the mean age of respondents was 35.8 years old. Most of the respondents were among moderate-income group with secondary education. Only 14.7% respondents scored high level of financial literacy, whereas 53.6% scored in high financial management practices, and 87% respondents scored moderate level in retirement confidence. There was 41.3% respondents had their own savings for retirement purpose. There was a significant difference in retirement confidence in term of saving motives (p<0.001) and marital status (p<0.01). Pearson Correlation indicated that there were significant relationships between financial literacy, financial management practices, and retirement confidence. The variables used in this study contributed 32.9% towards the model. Multiple regression result also showed that individual characteristics (marital status, education,and money adequacy), financial literacy, saving motives, and financial management practices have significant influence on retirement confidence, while saving motives is the strongest predictor of retirement confidence among working women. This study suggested that the findings are useful for the government to help working women in financial planning direction. Women could be more alert with the enhancement of their financial preparation in order to maintain their standard of living during retirement life. On the other hand, some financial education workshops could be provided by their workplaces’ management to help them to have better understanding in all kinds of financial aspects which could help them to make wise financial decisions. The determinants of retirement confidence would help working women to be more financial literate and be aware of the retirement preparedness in advance. By doing so,this could prevent or reduce women from facing issues regarding their financial inadequacy during retirement life.